A breakdown of metabolic reprogramming in microglia induced by CKLF1 exacerbates immune tolerance in ischemic stroke - Wen-yu Ma; Qing-lin Wu; Sha-sha Wang; Hong-yun Wang; Jun-rui Ye; Hong-shuo Sun; Zhong-ping Feng; Wen-bin He; Shi-feng Chu; Zhao Zhang; Nai-hong Chen (Journal of Neuroinflammation, 2023)
Abstract Ischemic stroke is characterized by the presence of reactive microglia. However, its precise involvement in stroke etiology is still unknown. We used metabolic profiling and showed that chemokine like factor 1 (CKLF1) causes acute microglial inflammation and metabolic reprogramming from oxidative phosphorylation to glycolysis, which was reliant on the AMP-activated protein kinase (AMPK)–mammalian target of rapamycin (mTOR)–hypoxia inducible factor 1α (HIF-1α) signaling pathway. Once activated, microglia enter a chronic tolerant state as a result of widespread energy metabolism abnormalities, which reduces immunological responses, including cytokine release and phagocytosis. Metabolically dysfunctional microglia were also found in mice using genome-wide RNA sequencing after chronic administration of CKLF1, and there was a decrease in the inflammatory response. Finally, we showed that the loss of CKLF1 reversed the defective immune response of microglia, as indicated by the maintenance its phagocytosis to neutrophils, thereby mitigating the long-term outcomes of ischemic stroke. Overall, CKLF1 plays a crucial role in the relationship between microglial metabolic status and immune function in stroke, which prepares a potential therapeutic strategy for ischemic stroke. Graphical Abstract